Analisis Potensi Ketersediaan Tanaman Bambu dan Pemasaran Kerajinan Bambu di Desa Kayubihi Kecamatan Bangli Kabupaten Bangli - PRATIWI, AYU RATIH; USTRIYANA, I NYOMAN GEDE; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p10, 2018)
The Potential Analysis Availability Of Bamboo Plants and The Marketing of Bamboos Product at Kayubihi Village, Bangli Distric, Bangli Regency. Analysis of the potential availability of bamboo plants in Kayubihi Village, Bangli Subdistrict, Bangli Regency is divided into two analyzes, namely the analysis of potential availability and marketing analysis. Analysis of potential availability to know the potency of bamboo found in Kayubihi Village while for marketing seen marketing channel, marketing margin, and profit margin with the election of three main products produced by Kayubihi Village. Types of data used in this study are qualitative data and quantitative data and data sources obtained from primary data and secondary data. Data collection methods used there are three namely Library research, field research and study literature. The population in this study were 50 bamboo farmers who were also bamboo craftsmen. Data analysis was done descriptively quantitative and qualitative descriptive. The results showed that the analysis of potential availability with five types of bamboo plants is under 200 clumps/ha which means not yet potential. Bamboo is processed into handicrafts and marketed for marketing the main products are sokasi, cakes basket, and coocked rice basked. Each product has three marketing channels. The most profit margin obtained in each marketing channel is at producer level. The shortest marketing margin in each channel because it is directly to the consumer.